2015
DOI: 10.1002/2015gl064326
|View full text |Cite
|
Sign up to set email alerts
|

The existence of radial anisotropy in Earth's upper inner core revealed from seismic normal mode observations

Abstract: As we strive to understand the most remote region of our planet, one critical area of investigation is the uppermost inner core since its structure is related to solidification of outer core material at the inner core boundary (ICB). Previous seismic studies have used body waves to show that the top ∼100 km of the inner core is isotropic. However, radial anisotropy cannot be uniquely determined by body wave observations. Alternatively, normal mode center frequencies are sensitive to spherically symmetric Earth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…Hence, the effect of the anisotropy on travel times would be undetectable. Lythgoe and Deuss (2015) also noted this in their study of center frequency shifts of inner core-sensitive normal modes.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…Hence, the effect of the anisotropy on travel times would be undetectable. Lythgoe and Deuss (2015) also noted this in their study of center frequency shifts of inner core-sensitive normal modes.…”
Section: Introductionmentioning
confidence: 78%
“…The form of anisotropy we chose, VTI, yields PKPdf travel times in the shallow inner core that do not vary with spin axis orientation. Hence, the ICB surface that, to travel times, appears to be isotropic (Garcia & Souriau, 2000;Ozounis & Creager, 2001) might not in fact be so, an insight that motivated Lythgoe & Deuss's (2015) study. Rather, solid crystallites might be oriented by compaction, flow, or electromagnetic forces uniformly upon adhesion to the ICB that could impart a uniform VTI fabric.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inner core is radially layered with a zone ~100‐km thick near its surface, where the axial anisotropy may be weaker (Ouzounis & Creager, ; Song & Helmberger, ; Waszek & Deuss, ) or more radially oriented (Lythgoe & Deuss, ), and an innermost inner core (IMIC) with a radius of 300–600 km (Beghein & Trampert, ; Ishii & Dziewoński, ), where the anisotropy may be stronger (Romanowicz et al, ; Sun & Song, ) and perhaps tilted with respect to the rotation axis (Niu & Chen, ; Wang et al, ). Inner‐core structure also varies with longitude (Creager, ; Irving et al, ; Tanaka & Hamaguchi, ), having an eastern hemisphere that shows substantially less anisotropy than its western hemisphere.…”
Section: Seismological Datamentioning
confidence: 99%
“…Since then, the inferred pattern of anisotropy has grown more complex, to include depth variations (Shearer, 1994), hemispherical variations (Tanaka & Hamaguchi, 1997), and regional variations (Koper et al, 2004). Some studies (Shearer, 1994) have found that the top of the inner core is isotropic, but Lythgoe and Deuss (2015) have instead suggested radial rather than cylindrical anisotropy. There are also suggestions of an innermost inner core with a different axis of anisotropy (Ishii & Dziewonski, 2003).…”
Section: Introductionmentioning
confidence: 99%